2016
DOI: 10.26578/jrti.v10i1.1752
|View full text |Cite
|
Sign up to set email alerts
|

Performa Pengeringan Kontinyu dan Terputus Pada Biji Kakao Fermentasi dengan Metode Pengeringan Lapis Tipis

Abstract: This study aims to determine the performance of a continuous and intermittent sun drying of fermented-cocoa bean by using thin-layer drying method. Continuous drying using a solar dryer finned-flat plate collector type which is operated in two modes drying time, daytime and night time. During the day, the cocoa beans are dried in the drying chamber using hot air generated by the solar collectors. In the nighttime, desiccant (CaCl2) was added to the drying chamber that had been isolated. Open sun drying as inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Other studies have shown that roasting temperature is directly proportional to the roasting rate [41]. The shortest baking time of 19 hours and the lowest moisture content of 4.40 and 3.41 were successively obtained from oven method roasting at 55 o C and 65 o C [41].…”
mentioning
confidence: 88%
See 3 more Smart Citations
“…Other studies have shown that roasting temperature is directly proportional to the roasting rate [41]. The shortest baking time of 19 hours and the lowest moisture content of 4.40 and 3.41 were successively obtained from oven method roasting at 55 o C and 65 o C [41].…”
mentioning
confidence: 88%
“…Other studies have shown that roasting temperature is directly proportional to the roasting rate [41]. The shortest baking time of 19 hours and the lowest moisture content of 4.40 and 3.41 were successively obtained from oven method roasting at 55 o C and 65 o C [41]. Roasting using an oven produces better quality cocoa beans in improving the quality of cocoa products with free fatty acid levels of 1.38% and 1.02% [41].…”
mentioning
confidence: 94%
See 2 more Smart Citations
“…Proses pengeringan dengan menggunakan tenaga surya tersebut dilakukan selama 3 hari. Dari penelitian tersebut disimpulkan bahwa metode yang digunakan hanya mampu beroperasi pada suhu 31-48 0 C sedangkan suhu optimal pengeringan adalah 55-65 0 C (Dina et al, 2013).…”
Section: Pendahuluanunclassified